Karzinome der Gallenwege: molekulare Charakterisierung und Identifikation neuer prognostischer Marker - Goeppert, Benjamin (Der Pathologe, 2017)
BackgroundBile duct cancers (BTCs) are highly aggressive tumors with a dismal prognosis and an increasing incidence. BTC is a tumorbiologically and clinically heterogeneous tumor group and can be subdivided according to anatomical aspects into intrahepatic cholangiocarcinomas (iCCA), extrahepatic cholangiocarcinomas (eCCA) and gallbladder carcinomas (GBC).New therapy optionsChronic inflammatory processes of the biliary system seem to play a role in the development of these tumors. Insights into molecular cholangiocarcinogenesis could make an important contribution to novel and more precise classification attempts and to the development of new, targeted therapies for BTC.Epigenetic and genetic alterations in cholangiocarcinomasThe first description of genome-wide DNA methylation patterns in CCA showed drastic global methylation differences between CCA and corresponding non-neoplastic tissue (matched-pair analyses). Moreover, significant methylation differences between the CCA subtypes (eCCA and iCCA) could be found. Using immunohistochemistry and Sanger sequencing, it was shown that the actual BRAF V600E mutation rate seems to be significantly lower (1.3%) than previously described in the literature.Immunephenotyping in biliary tract cancersA comprehensive, subtype-specific characterization of tumor-infiltrating immune cells as well as an expression analysis of Major Histocompatibility Complex I was performed in a large and well-characterized BTC cohort. For further studies on the efficacy of immunomodulatory therapy approaches for BTC, the presented results provide a solid basis.